PEMETAAN KETERAMPILAN DASAR MENGAJAR (KETERAMPILAN VARIASI) GURU TK DI KECAMATAN KERUMUTAN KABUPATEN PELALAWAN - Rana Yulis; Wilson Wilson; Febrialismanto Febrialismanto (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
Abstract: the aimed of this study to determine the variation of the skills taught kindergarten teachers in Kerumutan sub district Pelalawan regency. Population and samples in this study are amounted to 35 kindergarten teachers in Kerumutan sub district Pelalawan regency. The data collection techniques that use test works by means of observation sheets. The data analysis using the percentage formula. The results were obtained variations skills teaching kindergarten teacher in Kerumutan sub district Pelalawan regency obtain an overall percentage of 65.54% which is in good criteria. Based on the analysis of the level teacher education, it doesn’t affect the level of educational variation skills kindergarten teachers in Kerumutan sub district Pelalawan regency. It can be seen from the data analysis is based on the calculation of chi square turns a that numbers of 5.53 obtained. That numbers compared with the chi-square value in the table with dk 6 as 5% significance level that is equal to 12.592, the calculation result is smaller than the chi square chi square results in the table (5.53 <12.592). Based on an analysis of training, it doesn’t affect variation skill training kindergarten teachers in Kerumutan sub district Pelalawan regency. It can be seen from the data analysis is based on the calculation of chi square turns that numbers 7.73 was obtained. That numbers compared with the chi-square value in the table with dk 12 as 5% significance level that is equal to 21.026, the calculation result is smaller than the chi square chi square results in the table (7.73 <21.026).Keywords: Teaching basic skills, Variations skills